Disability and happiness: the role of social policies - Bellia, Asya (Università degli Studi di Siena, 2021)
Disabled people are less satisfied with their lives compared with nondisabled people. The first chapter of this doctoral thesis aims to understand how much of this differential is explained by the actual impairments disabled people have and how much by the barriers they face to a full participation in society. Contrasting evidence on the effect of education on subjective well-being (SWB) suggests that other factors, such as aspirations or income, might mediate the relationship between satisfaction and educational attainment. As regards working status, however, the positive impact of holding a job and the negative effect of being unemployed on individual happiness remain unquestioned (Di Tella et al., 2001; Frey & Stutzer; 2000; 2010). The data is taken from the European Survey on Income and Living Conditions (EU-SILC) for year 2013. The EU-SILC is an annual survey including 32 countries, the 28 European Member States and four additional countries (Iceland, Norway, Serbia and Switzerland), which is addressed to individuals aged 16 or older living in private households. In year 2013 only, it included an ad hoc module on well-being. Results show that disabled people are significantly less likely to be working, as well as less satisfied with their lives on average. Moreover, societal participation has a positive impact on subjective well-being. The disability policies of different OECD member states have been converging since 1990, with benefits getting progressively less generous, a tightening of eligibility criteria and increased emphasis on active labour market policies. Literature on the impact of reduced benefits and activation policies on the employment of disabled people is inconclusive. However, most of it analyzes either active or passive policies. The second chapter of this thesis focuses instead on the combined effect of different policies on disabled people's labour market attachment. Google scholar was used as a search engine and snowballing allowed to find additional papers. The literature was then ...